2022
DOI: 10.1186/s12957-022-02789-7
|View full text |Cite
|
Sign up to set email alerts
|

Value of different anastomoses in laparoscopic radical right hemicolectomy for right-sided colon cancer: retrospective study and literature review

Abstract: Background This study aimed to analyze the safety of circular lateral anastomosis and cross-lateral anastomosis in laparoscopic radical resection of right-sided colon cancer. Methods From January 2018 to March 2021, 147 patients with right-sided colon cancer were admitted to the Department of General Surgery, Cancer Hospital, Zhengzhou University. The experimental group comprised patients with circular lateral anastomosis, whereas the control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…Some suggest lower leakage rates in ETS compared to FETE, whereas others report no signi cant difference between the two. [11,15,[21][22][23] Our study found an overall anastomotic leakage rate of 0.66%, with no signi cant difference between FETE and ETS anastomosis, a nding that aligns with the generally lower rates of leakage observed in modern surgical practice due to improved stapler use and advanced techniques. [22,24,25] Appropriate stapler use and advanced surgical techniques may have contributed to the reduced rate of anastomotic leakage, leading to no signi cant differences in leakage rates between the different types of anastomosis.…”
Section: Discussionsupporting
confidence: 67%
“…Some suggest lower leakage rates in ETS compared to FETE, whereas others report no signi cant difference between the two. [11,15,[21][22][23] Our study found an overall anastomotic leakage rate of 0.66%, with no signi cant difference between FETE and ETS anastomosis, a nding that aligns with the generally lower rates of leakage observed in modern surgical practice due to improved stapler use and advanced techniques. [22,24,25] Appropriate stapler use and advanced surgical techniques may have contributed to the reduced rate of anastomotic leakage, leading to no signi cant differences in leakage rates between the different types of anastomosis.…”
Section: Discussionsupporting
confidence: 67%